2007
DOI: 10.1037/0022-0167.54.3.224
|View full text |Cite
|
Sign up to set email alerts
|

Critical issues in the measurement of ethnic and racial identity: A referendum on the state of the field.

Abstract: Ethnic and racial identity are among the most researched topics in the multicultural counseling literature. The popularity of these constructs, combined with ongoing controversies surrounding their measurement, warrants a critical examination by scholars in the field. The author contends that a combination of science and ideology has influenced the field and warns that a rigid and uncritical adherence to old paradigms will stifle growth and the production of useful knowledge. The author provides a review of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
317
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(328 citation statements)
references
References 86 publications
8
317
2
1
Order By: Relevance
“…This reciprocal relationship has been repeatedly supported by research (Cokley, 2007 Consequently, their results showed that the students in these studies endorsed academic race stereotypes.…”
Section: Academic Self-conceptsupporting
confidence: 49%
“…This reciprocal relationship has been repeatedly supported by research (Cokley, 2007 Consequently, their results showed that the students in these studies endorsed academic race stereotypes.…”
Section: Academic Self-conceptsupporting
confidence: 49%
“…Thus, we view racial identity as a core aspect of an individual's sense of ethnic identity. However, the question of whether the construct of racial identity can be subsumed within the broader construct of sense of ethnic identity (thus implying that the conceptualization and measurement of sense of ethnic identity among members of various ethnic groups should take priority over the conceptualization and measurement of racial identity among members of a particular racial group) is a matter of ongoing debate (e.g., Cokley, 2007;Helms, 2007;Phinney & Ong, 2007).…”
Section: Goffman's Interactionist Role Theorymentioning
confidence: 99%
“…At the time that we conducted the present studies, we opted not to include Roberts et al's (1999) 12-item MEIM alongside our expanded MEIM, due to concerns that participants would conflate the terms race/racial and ethnicity/ethnic (a matter of considerable debate among researchers within ethnic psychology; e.g., Cokley, 2007;Helms, 2007;Phinney & Ong, 2007) In addition, at the time that we conducted the present studies, Schwartz et al's (2012) AIM had not been published. However, within the United States, future researchers might wish to substitute the AIM for the national identity scale within our expanded MEIM in order to determine whether American identity in particular is related to racial and religious identities (keeping in mind that the AIM, like our expanded MEIM, measures exploration and commitment as dual developmental themes).…”
Section: Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Although race and ethnicity are socially constructed concepts (Cokley, 2007;Trimble, 2007), there has been significant research on the structural components of exploration and resolution/commitment leading to achievement of an ethnic identity (Phinney & Ong, 2007;Yoon, 2011). Further, ethnic identity is developed at both the individual level and at the collective level due to interaction with society (Yoon, 2011), therefore environmental context is important.…”
Section: Enculturation and Acculturationmentioning
confidence: 99%